Changes in Norges Bank's Role and Activities in Cash Supply and Distribution - Trond Eklund; Svein Nygard; Leif Veggum (Norges Bank, 2017)
Norges Bank has made considerable changes in its role and activities in cash supply and distribution since the turn of the century, with the aim of enhancing efficiency in cash distribution and the payment system as a whole. Norges Bank's cash distribution responsibilities have been clarified, and the Bank has assumed a defined role as wholesaler. In addition, Norges Bank has outsourced note and coin processing services to a considerable extent compared with other central banks and currently relies on purchasing these services from external operators. This article presents the changes and reviews the assessments and reasoning behind the choices made in the light of Norges Bank's responsibilities. The final section examines the consequences of the changes. The overall assessment is that the changes have increased efficiency in the cash supply and enhanced efficiency in the payment system as a whole.
hdl:11250/2506372; Additional information: This Staff Memo is a slightly adjusted version of an article published in Norwegian in 2010. Due to great interest of colleagues from other central banks, we present the changes in the Norwegian cash cycle in English.
Keywords: 330